2017
DOI: 10.1175/jpo-d-16-0200.1
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Upper-Ocean Mixing Affected by Meltwater Layers during Arctic Summer

Abstract: Every summer, intense sea ice melt around the margins of the Arctic pack ice leads to a stratified surface layer, potentially without a traditional surface mixed layer. The associated strengthening of near-surface stratification has important consequences for the redistribution of near-inertial energy, ice-ocean heat fluxes, and vertical replenishment of nutrients required for biological growth. The authors describe the vertical structure of meltwater layers and quantify their seasonal evolution and their effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 46 publications
6
47
0
Order By: Relevance
“…During this event, significant turbulent mixing was observed in the ocean surface layer in response to the strong winds, but this mixing did not break through the seasonal pycnocline at ~20 m even during the strongest winds on 18–19 September (Figure b). This is consistent with previous studies by Randelhoff et al (, ), who reported a rapid attenuation in the turbulent mixing at the seasonal pycnocline. On the other hand, strong mixing was observed down to depths of 20–30 m below the seasonal pycnocline on 11–12 September, despite the wind being calm.…”
Section: Discussionsupporting
confidence: 94%
“…During this event, significant turbulent mixing was observed in the ocean surface layer in response to the strong winds, but this mixing did not break through the seasonal pycnocline at ~20 m even during the strongest winds on 18–19 September (Figure b). This is consistent with previous studies by Randelhoff et al (, ), who reported a rapid attenuation in the turbulent mixing at the seasonal pycnocline. On the other hand, strong mixing was observed down to depths of 20–30 m below the seasonal pycnocline on 11–12 September, despite the wind being calm.…”
Section: Discussionsupporting
confidence: 94%
“…Overall, there was an 80% increase in internal wave amplitude between full ice cover (amplitudes of 0.7 m at C2–C4 in March to 26 April) and open water (1.3 m for Seagliders in August–September), greater than the seasonal cycle documented in Dosser and Rainville () as that measure includes a variety of ice concentrations in the summer season. The open water conditions observed by the Seagliders had amplitudes 20% larger than the low ice concentration conditions observed at C2, consistent with past studies showing less dramatic contrasts between low ice concentrations and open water conditions (Randelhoff et al, ). The specific mechanism that results in increased energy between low ice concentrations and open water is unclear; decreased dissipation at the surface (due to absence of rough ice or a lack of any ice) or increased local generation is plausible.…”
Section: Discussionsupporting
confidence: 89%
“…From our observations, Richardson number provides only some constraints on the possible variations in vertical mixing. The 4‐m Richardson number was almost always larger than 1/4 during the MIZ field program, consistent with the paradigm of weak turbulent diapycnal diffusivities in the Arctic (e.g., Fer, ; Guthrie et al, ; Lincoln et al, ; Randelhoff et al, ). Lower values were observed for rougher ice and lower ice concentrations, suggesting that vertical mixing may be sensitive to changes in the ice cover.…”
Section: Discussionsupporting
confidence: 76%
“…First, the convection driven entrainment is presumably even smaller than that given by Randelhoff and Guthrie []. Second, upper halocline waters have to be renewed either through a convective‐advective mechanism [ Rudels et al ., ] to achieve an interannual steady state, or by upward diffusion of deeper halocline waters during summer when surface meltwater restricts vertical mixing to above upper halocline waters [ Randelhoff et al , ].…”
Section: Discussionmentioning
confidence: 99%